The Effect of KNO3 Addition on the Properties of Coconut Shell Charcoal Briquettes - Achmad Erlangga Bintang Samodra; samsudin anis; janviter manalu; Al Ichlas Imran; Januar Parlaungan Siregar; Tezara Cionita; Fitriyana, Deni Fajar (Jurnal Bahan Alam Terbarukan, 2025)
This research investigates the effects of incorporating potassium nitrate (KNO₃) into coconut shell charcoal briquettes, emphasizing their physical and chemical characteristics. Briquettes were manufactured utilizing coconut shell charcoal powder, tapioca flour as a binder, and different concentrations of KNO₃ (0% and 10%) as an additive. The aim was to assess the impact of KNO₃ incorporation on the water content, ash content, volatile matter, fixed carbon, calorific value, and density of the briquettes. The findings indicated that incorporating KNO₃ resulted in elevated water and ash content, adversely affecting combustion efficiency. Briquettes with increased water content demonstrated reduced mechanical strength and inferior combustion performance. The addition of KNO₃ led to an increased volatile matter content, facilitating ignition of the briquettes while simultaneously resulting in higher smoke emissions. The addition of KNO₃ resulted in a decrease in fixed carbon content, which subsequently lowered the calorific value of the briquettes. The formulation without KNO₃ produced the densest briquette, suggesting that including KNO₃ reduced the briquette density. The inclusion of KNO₃ enhances ignition characteristics; however, it concurrently diminishes the briquettes' overall quality regarding combustion efficiency and calorific value. The Briquette B_1 exhibited the highest results in this investigation, with water content, ash content, volatile matter, fixed carbon content, calorific value, and density values of 4.97%, 1.87%, 17.25%, 80.88%, 7014 Cal/g, and 0.90 g/cm³, respectively.